Determination of association constants towards carbon nanotubes. Issue 12 (15th September 2015) - de Juan, Alberto; López-Moreno, Alejandro; Calbo, Joaquín; Ortí, Enrique; Pérez, Emilio M.
Abstract : We describe a simple procedure for the determination of association constants between soluble molecules and insoluble and heterogeneous carbon nanotube samples. Abstract : Single-walled carbon nanotubes (SWNTs) are one of the most promising nanomaterials and their supramolecular chemistry has attracted a lot of attention. However, despite well over a decade of research, there is no standard method for the quantification of their noncovalent chemistry in solution/suspension. Here, we describe a simple procedure for the determination of association constants ( K a ) between soluble molecules and insoluble and heterogeneous carbon nanotube samples. To test the scope of the method, we report binding constants between five different hosts and two types of SWNTs in four solvents. We have determined numeric values of K a in the range of 1–10 4 M −1 . Solvent effects as well as structural changes in both the host and guest result in noticeable changes of K a . The results obtained experimentally were validated through state-of-the-art DFT calculations. The generalization of quantitative and comparable association constants data should significantly help advance the supramolecular chemistry of carbon nanotubes.